Implementation of Environmental Hygiene and Sanitation in Deli Tua Market, Deli Serdang District - Prasetyo, Angga Dwi; Lubis, Irwansyah; Lauchan, Agil Maritho; Munthe, Ni’matul Ulya; Putra MS, Saidana Wahyudi (Universitas Ibn Khaldun Bogor, 2025)
The market is a public facility that involves many people and physical interactions that can be a means of spreading disease. Further research is needed because the initial observation results show non- compliance with PERMENKES RI No. 17 of 2022 in terms of the application of personal hygiene, spatial arrangement, drainage, and market buildings. The purpose of this study is to analyze the extent of the application of environmental hygiene and sanitation in the Old Deli Market. This research uses qualitative methods with descriptive type research, and data collection using direct observation, in-depth interviews, and documentation. The selection of key informants in this study used purposive sampling method. The results showed that Deli Tua Market has not met the requirements of a healthy market according to PERMENKES RI No. 17 of 2020. Waste management facilities are still smelly and scattered. Clean water facilities are not available by the market manager. Vector control facilities have never been sprayed every month. Hand washing facilities are not available and are not equipped with soap and running water. The application of personal hygiene of traders is not in accordance with the requirements such as incomplete PPE, smoking, spitting, littering in the market environment and not washing hands while the hygiene of traders meets the requirements and drainage channels also meet the requirements because the drainage channels are cemented and covered with gratings and metal and drainage channels are smooth.